Protecting Refugees Against Human Trafficking - Jun Justinar (Faculty of Law, Trisakti University, 2017)
When governments are unwilling or unable to protect their citizens, individuals may suffer such serious violations of their personal rights. The hallmark of a refugee is the absence of protection by his own state. Refugees are at particular risk for human trafficking as a consequence of their vulnerable status. There are some instruments to protect refugee from human trafficking. In the frame of trafficking, refugees then have a double protection due to their status, first the Convention on the Status of Refugee; and second by the international instruments related to Human Trafficking. The principle of non-refoulement constitutes an essential component of international refugee protection and also embodied in some regional instruments. Providing temporary protection is a humanitarian and non-political act to react speedily to a crisis or disaster, including to prevent human trafficking on refugee. It is the duty and responsibility of all States to cooperate in all the fields in which international cooperation could be develop in solving international problems especially on refugee.